Analisis Determinan Underpricing Saham di Bursa Efek Indonesia - Adhi Partama, I Gusti Ngurah; Gayatri, Gayatri (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
The purpose of this study is to test and analyze the variables that affect the level of underpricing in companies that conduct IPOs. These variables are the percentage of shares offered, company size, return on equity, current ratio, and debt to equity ratio. This study uses a multiple linear regression analysis method. The type of data used is secondary data. The population of this study was 121 companies that conducted IPOs on the Indonesia Stock Exchange in 2013-2017. Sampling uses purposive sampling technique, so that the sample obtained in this study were 72 companies. The results showed that partially, firm size variables had a significant negative effect on underpricing and the return on equity variable had a significant negative effect on underpricing. Other variables, namely the percentage of shares offered, the current ratio, and the debt to equity ratio partially do not affect underpricing. Keywords : Underpricing, return on equity, current ratio, debt to equity ratio